Performance Comparison of Enterprise Applications on Mobile Operating Systems - Adrian Mullally; Nigel McKelvey; Kevin Curran (Universitas Ahmad Dahlan, 2011)
Due to the advances in mobile phone technology, Smartphones have the ability to access web services within applications the user interacts with to retrieve and send information from and to web services. As Smartphones have grown in popularity, the utilisation of both new web services and web services already in place will also grow. This paper provides a comparison of the two main types of web services, SOAP and REST. We evaluate the performance of using SOAP and REST on a smartphone. The tests performed include the time taken to perform a web service call, the RAM used making a web service call and the data transmitted and received while making a web service call.